High kelp density attracts fishes except for recruiting cryptobenthic species. (October 2020) - Shelamoff, Victor; Layton, Cayne; Tatsumi, Masayuki; Cameron, Matthew J.; Wright J, Jeffrey T.; Edgar, Graham J.; Johnson, Craig R.
Abstract: As foundation species, kelp support productive and species rich communities; however, the effects of kelp structure on mobile species within these complex natural systems are often difficult to assess. We used artificial reefs with transplanted kelp to quantify the influence of kelp patch size and density on fish assemblages including the arrival of recruiting cryptobenthic species. Large patches with dense kelp supported the highest abundance, species richness, and diversity of fishes, with the addition of dense kelp tripling biomass and doubling richness. The abundance of recruits in artificial collectors declined with patch size and was halved on reefs with sparse kelp compared to reefs with dense kelp or no kelp. These results highlight the importance of dense kelp cover in facilitating biodiversity and indicate that kelp addition could support the recovery of degraded coastal ecosystems. Kelp also apparently drives complex interactions affecting the recruitment/behaviour of some cryptobenthic species. Highlights: Adding dense kelp to artificial reefs tripled fish biomass and a doubled species richness. Kelp did not increase the abundance of recruiting cryptobenthic species. Adding kelp to natural and artificial reefs may mitigate some effects of habitat decline on coastal biodiversity.